ASSOCIATION OF FATAL AND NONFATAL CARDIOVASCULAR OUTCOMES WITH 24 HOUR MEAN ARTERIAL PRESSURE. (April 2021) - Melgarejo, Jesus; Yang, Wen-Yi; Thijs, Lutgarde; Li, Yan; Asayama, Kei; Hansen, Tine; Kikuya, Masahiro; Ohkubo, Takayoshi; Dolan, Eamon; Stolarz-Skrzypek, Katarzyna; Huang, Qi-Fang; Tikhonoff, Valérie; et al.
Abstract : Objective: Automated oscillometric devices are increasingly replacing auscultation for assessment of systolic (SBP) and diastolic (DBP) blood pressure, but determine mean pressure (MAP) and extrapolate SBP and DBP. Major adverse cardiovascular events (MACE) are closest associated with 24 H blood pressure levels. We determined outcome-driven 24 H MAP thresholds and assessed association of MAP, SBP and DBP with MACE. Design and method: In a population-based cohort (n = 11, 596), blood pressure and risk factors were measured at baseline. Office MAP, computed from SBP and DBP, was categorized according to the 2017 American guideline. 24 H MAP was recorded oscillometrically. Statistics included multivariable Cox regression and the log-likelihood ratio test. Results: Baseline office and 24 H MAP averaged 97.4 and 90.1 mm Hg. Over 13.6 years (median), 2034 MACE occurred. 24 H MAP levels of < 90, 90–92, 93–96 and = > 96 mm Hg yielded equivalent 10 year MACE risks as the office MAP standard and delineated normotension (n = 6304), elevated 24 H MAP (n = 1074), and hypertension stages 1 (n = 1732) and 2 (n = 2484). MACE rates per 1000 person-years increased (P < 0.001) with higher 24 H MAP category from 11.9 (95% CI, 11.1–13.2) to 12.5 (10.7–14.7), 16.2 (14.6–18.1) and 22.0 (20.4–24.1). Compared with 24 H MAP normotension, the corresponding hazard ratios were 1.06 (0.88–1.25), 1.43 (1.26–1.63) and 1.78 (1.59–2.00). Adding 24 H MAP to covariables, SBP and DBP improved the model fit (P < 0.001). On top of MAP, higher SBP increased, whereas higher DBP attenuated risk (P < 0.001). Conclusions: The oscillometrically determined 24 H MAP used in conjunction with SBP and DBP substantially refined estimates of MACE risk.